Facile Construction and In Silico Study of Quinoline‐Attached Resorcinarene Fluorescent Sensor for the Recognition of Insensitive Munition Compounds. Issue 45 (5th December 2018) - Panchal, Urvi; Modi, Krunal; Liska, Alan; Ludvik, Jiri; Dey, Shuvankar; Patel, Chirag; Jain, V. K.
Abstract: N‐methyl‐4‐nitroaniline (MNA), an insensitive munition is selectively and sensitively recognized by a new resorcinarene bearing quinoline moiety, i.e, Tetra‐Methoxy Resorcinarene Tetra‐Quinoline Acetamide (TMRTQA). A simple and efficient spectrofluorimetric technique demonstrates the quenching of the fluorescence intensity of TMRTQA upon addition of MNA within concentration limits of 2 nM to 1 μM. Binding constant and quantum yield have been determined in this study. Molecular docking studies have been performed to predict the best binding affinity and the possible interactions for the formation of complex between TMRTQA and MNA supporting the 1:1 stoichiometry. Density functional theory calculation also support the excitation wavelength and geometry optimization. MNA being a hazardous environmental pollutant has been successfully detected from the water sample by standard addition method. Abstract : A new resorcinarene bearing four quinoline moieties (TMRTQA) has been synthesized for the selective and sensitive molecular recognition of N‐methyl‐4‐nitroaniline (MNA) that behaves as a fluorescent sensor within the concentration limits of 2 nM to 1 μM and its chemo‐informatics analysis has also been performed.